Mangrove composition and anthropogenic marine debris survey in Camotes Group of Islands, Philippines - Maximino III Abejo; Arnel Nudalo; Martha Joyce Garciano; Ian Paul Bayon; Chembelyn Gella Bayon; Marvin Guinocor; Jesrael Linao; Althea Mae Guevara; Christine Caya; Sylvester Tan Cortes (Environmental Challenges)
Mangrove forests provide vital economic and socio-ecological functions, including shoreline protection, nursery, and habitat provision for marine biodiversity, carbon sequestration, water purification, livelihood support, and preservation of traditional and cultural values. However, these ecosystems are increasingly threatened by natural forces and anthropogenic pressures, particularly the accumulation of Anthropogenic Marine Debris (AMD). While AMD deposition has been documented globally, data remain limited and geographically restricted, especially in smaller island systems where tourism and coastal development are rapidly expanding. This study surveyed AMD deposition and mangrove species composition in the Camotes Group of Islands, an emerging tourism hub in the Philippines, with the goal of informing localized conservation planning. Fieldwork was conducted in four municipalities: Tudela (S1), Poro (S2), San Francisco (S3), and Pilar (S4), using 15 quadrats (10×10 m each) per site, distributed across seaward, midward, and landward zones along five perpendicular transects. A total of 11 mangrove species were identified, comprising eight true mangroves and three mangrove associates. The families Rhizophoraceae and Lythraceae were the most represented. Notably, two species, Sonneratia ovata (near threatened) and Avicennia rumphiana (vulnerable), were recorded, indicating the urgency of focused conservation efforts. Across the 6000 m² study area, 2003 AMD items weighing 102.886 kg were documented, with plastics (e.g., packaging, beverage containers, food wrappers) accounting for the majority. Although the total debris volume was lower than reported in heavily urbanized regions, the consistent presence of AMD in all sites highlights the urgent need for locally tailored interventions. Based on these findings, the study recommends targeted and evidence-based strategies tailored to the Camotes Group of Islands context. These include establishing community-based monitoring programs, launching plastic waste reduction campaigns, restoring debris-impacted mangrove areas, and aligning local actions with national marine litter policies. Enhanced public awareness and inter-agency collaboration will be crucial to sustaining the ecological integrity of mangrove ecosystems and supporting the livelihoods of coastal communities in the Camotes Group of Islands.